2022
DOI: 10.3390/biology11111585
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long-Term Moderate Static Magnetic Field Exposure on Adult Female Mice

Abstract: Because of the high cost and safety of ultra-high magnetic resonance imaging (MRI), its application has certain limitations. Whereas 0.5–3 T MRI has been widely applied in hospitals, static magnetic fields (SMFs) have been shown to improve mice mental health and have anti-tumor potentials. Here, we compared the effects of the upward and downward 150 mT SMF groups with the sham group on C57BL/6J adult female mice. Locomotor and exploratory activity were also measured by behavioral tests, including the open fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…In addition to the tumor inhibition effects, Tian et al (19) found that 200 h exposure to 9.4 T SMF can reduce the toxicity of low-dose imatinib mesylate, and Yu et al (20) found that 24 days (24 h/day) of exposure to moderate SMF can also reduce cisplatin side effects in kidney. In addition, our previous study showed that 150 mT exposure for 18 weeks continuously reduces the anxiety-like emotion (31). Compared with the sham group, the present behavioral experiments showed that PD reduced the anxiety-like emotion in tumor-bearing mice, but neither 150 mT or 22 T ultra-high SMFs ameliorated this phenomenon, suggesting that SMFs disturbed this effect.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In addition to the tumor inhibition effects, Tian et al (19) found that 200 h exposure to 9.4 T SMF can reduce the toxicity of low-dose imatinib mesylate, and Yu et al (20) found that 24 days (24 h/day) of exposure to moderate SMF can also reduce cisplatin side effects in kidney. In addition, our previous study showed that 150 mT exposure for 18 weeks continuously reduces the anxiety-like emotion (31). Compared with the sham group, the present behavioral experiments showed that PD reduced the anxiety-like emotion in tumor-bearing mice, but neither 150 mT or 22 T ultra-high SMFs ameliorated this phenomenon, suggesting that SMFs disturbed this effect.…”
Section: Discussioncontrasting
confidence: 51%
“…Most of the time, they are exposed to 150-200 mT SMF, or even less (2). Therefore, the present study selected 150 mT SMF for the experiment and the exposure system is the same as our previous reports (31). Briefly, the magnetic plate used in mice experiment was composed of 10 small magnetic plates, each small magnetic plate contained eight north polar magnets, which strength were 500 mT, and formed the upward 150 mT magnetic plate to the surface of mice.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic field exposure improved lifespan and healthspan in mice (Fan et al, 2022). Static magnetic fields have been shown to improve mice mental health (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%